2022
DOI: 10.3390/jcm11072037
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Pittsburgh Sleep Quality Index (PSQI) in Patients with Multiple Sclerosis: Factor Structure, Reliability, Correlates, and Discrimination

Abstract: Sleep disturbances and poor sleep are a common complaint in the population with multiple sclerosis (MS) disease. The most commonly reported scale is the Pittsburgh Sleep Quality Index (PSQI), measuring seven components of sleep quality. Yet, till today, the PSQI instrument has not been validated in people with multiple sclerosis (pwMS). The objective of our study was to add precision in sleep quality assessment by investigating the psychometric properties of PSQI (factor structure, reliability, validity based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
2
13
1
Order By: Relevance
“…The EDSS score was used in the study to determine the severity of MS for quantifying the neurological disability. Further classification of MS patients was done, with an EDSS score less than 3.5 reflecting mild and moderate disability and an EDSS score greater than or equal to 3.5 reflecting severe disability. The control group included 50 individuals of the same age and gender who had no history of neurological or autoimmune illnesses. All subjects provided written informed permission when they were enrolled.…”
Section: Subjects and Methodsmentioning
confidence: 99%
“…The EDSS score was used in the study to determine the severity of MS for quantifying the neurological disability. Further classification of MS patients was done, with an EDSS score less than 3.5 reflecting mild and moderate disability and an EDSS score greater than or equal to 3.5 reflecting severe disability. The control group included 50 individuals of the same age and gender who had no history of neurological or autoimmune illnesses. All subjects provided written informed permission when they were enrolled.…”
Section: Subjects and Methodsmentioning
confidence: 99%
“…To date, the PSQI has been translated and validated in more than 40 countries, including Brazil [17], Colombia [18], Nigeria [19], China [20], Japan [21], Portugal [22], Italy [23], Germany [24], and Spain [25]. It has also been validated in different populations, such as adolescents [26], older adults [27,28], kidney transplant recipients [29], fibromyalgia patients [30], multiple sclerosis patients [31], breast cancer patients [32], patients with chronic pain [33], and women with post-traumatic stress disorder [34], among others. However, to the best of our knowledge, its psychometric properties have never been validated in the non-professional caregiver population.…”
Section: Introductionmentioning
confidence: 99%
“…The original version of the PSQI assumed that a global score representing overall sleep quality was sufficient to capture the multifaceted nature of the sleep problems that the instrument identified. However, since the first published research on the dimensionality of the instrument [27], numerous subsequent studies have reported various factor structures that support the existence of one factor (e.g., [26,32,33,35,36]), two factors (e.g., [28,30,31,37,38]), and three factors (e.g., [27,29,34,39,40]). Thus, there is no consensus on the factor structure, nor is there any study that has analyzed the factor structure of the PSQI in the population of nonprofessional caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep parameters including night sleep onset time, night sleep duration, night sleep latency, and PSQI score were obtained by the PSQI questionnaire. PSQI is a reliable self-report tool used to assess patients' sleep quality over the past month ( 24 ), and its results involve scores on seven components, including sleep quality, sleep latency, sleep duration, sleep efficiency, sleep disorders, sleep medications, and daytime sleep disorders ( 25 ). Physical activity was obtained through the international physical activity questionnaire (IPAQ).…”
Section: Methodsmentioning
confidence: 99%